2020
DOI: 10.1139/cjas-2019-0126
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, carcass characteristics, and meat quality of Mongolian lambs fed native grass or hay with or without concentrate on the Inner Mongolian Plateau

Abstract: The aim of this study was to evaluate the effects of native grass on growth performance, carcass characteristics, and meat quality of Mongolian lambs fed Inner Mongolia native grass in three forms: grass, hay, and hay with concentrate (HC). Sixty Mongolian noncastrated male lambs, in good health and with the same age (6 mo) and similar body weights (mean, 28.63 ± 0.19 kg), were randomly divided into three treatments. There were four replicates in each treatment, with five lambs in one pen as a replicate. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…(2019) and Du et al. (2020) who found pellets and HC could improve the carcass weight than fed with hay. The loin eye area is also highly correlated with carcass weight, and this region is used as an indicator of muscle development and carcass meat quantity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…(2019) and Du et al. (2020) who found pellets and HC could improve the carcass weight than fed with hay. The loin eye area is also highly correlated with carcass weight, and this region is used as an indicator of muscle development and carcass meat quantity.…”
Section: Discussionmentioning
confidence: 96%
“…The native grassland on the Inner Mongolia can provide 13.62 million tons of hay, which maintains approximately 42% of animal feed requirements in the winter and early spring (Hou et al., 2017). However, seasonal oscillation and climatic variability can affect grass quantity, nutritional quality, and availability and, as a consequence, constraint the livestock production and affect capacity to achieve their productive potential (Nardone et al., 2010) by exhibiting stronger in summer, fatter in autumn, thinner in winter, and weaker (which can lead to death) in spring (Du et al., 2020). The nutrient is an important factor for animal's growth performance (Sun, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Native grass is an herb that grows on native grasslands, which are widely scattered across the Mongolian Plateau; large needlegrass ( Stipa grandis P. Smirn) and Chinese leymus [ Leymus chinensis (Trin.) Tzvel] dominate typical steppe communities ( Zhang et al, 2016 ), are mostly utilized for grazing and haymaking, and are the main source of forage in pastoral areas ( Du S. et al, 2020 ). Seasonal changes affect the quality and productivity of native grass ( Kang et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…But the native grass hay is used as feed for ruminants alone resulting in an imbalance between supply and demand of energy because of the lower nutrient and harsh weather in winter. Previous studies have demonstrated that supplementary with concentrate could improve growth performance and carcass characteristics ( Du et al, 2020 ; Bu et al, 2021 ). In addition, the pelleted diet-fed lambs could also improve the growth performance and carcass characteristics by enhancing dry matter (DM) and energy intake, which shake off the disadvantages of feeding native grass directly ( Du et al, 2020 ; Zhou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that supplementary with concentrate could improve growth performance and carcass characteristics ( Du et al, 2020 ; Bu et al, 2021 ). In addition, the pelleted diet-fed lambs could also improve the growth performance and carcass characteristics by enhancing dry matter (DM) and energy intake, which shake off the disadvantages of feeding native grass directly ( Du et al, 2020 ; Zhou et al, 2022 ). Furthermore, replacing alfalfa hay with dry corn gluten feed and Chinese wild ryegrass can effectively increase the DM intake and promote microbial crude protein (CP) synthesis for ruminants ( Hao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%